2020
DOI: 10.1109/access.2020.2997921
|View full text |Cite
|
Sign up to set email alerts
|

A Physics-Based Neural-Network Way to Perform Seismic Full Waveform Inversion

Abstract: Seismic full waveform inversion is a common technique that is used in the investigation of subsurface geology. Its classic implementation involves forward modeling of seismic wavefield based on a certain type of wave equation, which reflects the physics nature of subsurface seismic wavefield propagation. However, obtaining a good inversion result using traditional seismic waveform inversion methods usually comes with a high computational cost. Recently, with the emerging popularity of deep learning techniques … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(11 citation statements)
references
References 43 publications
(38 reference statements)
0
11
0
Order By: Relevance
“…To determine whether two objects are related to one another, our proposed relationship proposal module is built on the feature extraction of the image module. The proposed relationship contains a multihead scaled dot-product attention sublayer [ 26 ], layer normalization [ 27 ], and N fully connected layers, where N is set to 3. The feature embedding of the feature extraction of an image module is denoted as , where K is the number of initial object-pairs.…”
Section: Approachmentioning
confidence: 99%
“…To determine whether two objects are related to one another, our proposed relationship proposal module is built on the feature extraction of the image module. The proposed relationship contains a multihead scaled dot-product attention sublayer [ 26 ], layer normalization [ 27 ], and N fully connected layers, where N is set to 3. The feature embedding of the feature extraction of an image module is denoted as , where K is the number of initial object-pairs.…”
Section: Approachmentioning
confidence: 99%
“…velocity model obtained by using reverse-mode AD is the same as that computed in the adjoint state method. Yet other similar approaches were proposed in [60,61,62]. In [63], the authors improved upon [56] to perform inversions simultaneously for multiple parameters in elastic isotropic and anisotropic media.…”
Section: Unsupervised Learning Approaches For Fwimentioning
confidence: 99%
“…Convolutional neural networks (CNN) are getting more and more popular in geophysical applications, typically in classification and segmentation tasks [12], [13], [14], [15], and [16]. Moreover, recent studies have demonstrated the feasibility of geophysical modeling using CNNs [17], [18], and [19]. Fig.…”
Section: B Generative Adversarial Network (Gan)mentioning
confidence: 99%